Perancangan Media Animasi Edukatif Mengenai Konsumsi Makanan Ekonomis dan Bergizi Untuk Ibu Hamil Dalam Pencegahan Stunting: Pendekatan Desain Komunikasi Visual - Tamara, Jihan; Resmisari, Ganis (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Educational animation media based on the theory of Visual Communication Design can increase pregnant women's understanding of the consumption of economical food with balanced and sufficient nutrition to meet the nutrition of the mother and the baby for stunting prevention in Indonesia. Mixed method with sequential explanatory design was used to conduct this study, the quantitative stage was carried out, namely pre-post test design on 31 pregnant women, and focus group discussion media evaluation was used for the qualitative stage. The animation design is based on Paivio's Dual Coding Theory, Cognitive Load Sweller Theory, and Mayer's Multimedia Learning Theory, with the application of semiotic and gestalt elements in visual design (Schwarzenberg et al., 2018). The 5-minute educational animation media is designed with the main segments, namely the introduction of 1000 HPK, the exposure of nutritious economical local foodstuffs, the importance of exclusive breastfeeding and motivation for behavior change, the importance of the role and support of family in fulfilling nutrition for pregnant women and correcting stigmas or myths circulating in the community regarding nutrition. With the Visual Communication Design approach, it has been proven to be effective in helping to increase the knowledge and motivation of pregnant women in fulfilling nutrition for stunting prevention. The integration of dual coding theory and multimedia learning in animation design produces media that is communicative, informative, and appropriate to the socio-economic context community.